2002
DOI: 10.1002/cpp.333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of empirically‐derived and rationally‐derived methods for identifying patients at risk for treatment failure

Abstract: Several systems have been developed to monitor and feedback information about a patient's responses to psychotherapy as a method of enhancing patient outcome. Feedback is generated from decision rules based on a patient's expected level of progress. Those patients who do not make expected levels of progress or whose progress in therapy is less than adequate are referred to as signal-alarm cases. Research has shown that feedback based on rationally-derived identification procedures increased the duration of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 34 publications
6
132
2
Order By: Relevance
“…Finch et al [13] developed and tested the accuracy of predicting deterioration in adults. These and related signal alarm systems have been evaluated in a number of empirical investigations [14,15,16,17]. This research shows that 85-100% of patients who deteriorate in treatment can be accurately identified prior to departing from treatment and often after the first few sessions of treatment.…”
Section: One Necessary Component Of Maximizing Patient Outcomementioning
confidence: 99%
“…Finch et al [13] developed and tested the accuracy of predicting deterioration in adults. These and related signal alarm systems have been evaluated in a number of empirical investigations [14,15,16,17]. This research shows that 85-100% of patients who deteriorate in treatment can be accurately identified prior to departing from treatment and often after the first few sessions of treatment.…”
Section: One Necessary Component Of Maximizing Patient Outcomementioning
confidence: 99%
“…The exact cutoff scores for determining how much change and by which session of therapy, and taking into account the initial OQ-45 score, were based on expert judgments and information on dose-response analysis, survival analysis, and hierarchical linear modeling (Lambert, Hansen, & Finch, 2001). These cutoff scores were established by Lambert, Whipple, Bishop, et al (2002) independently and before the current study.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…The decision rules were based on a client's intake score (initial level of disturbance), number of treatment sessions completed, and amount of change noted at the most recent session compared with the initial score. For a full description of the development and implementation of the decision rules, refer to Lambert, Whipple, Bishop, et al (2002). The exact cutoff scores for determining how much change and by which session of therapy, and taking into account the initial OQ-45 score, were based on expert judgments and information on dose-response analysis, survival analysis, and hierarchical linear modeling (Lambert, Hansen, & Finch, 2001).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…The prior study analyzing differential accuracy of a rational versus an empirical method in predicting psychotherapy outcome (Lambert et al, 2002a) also utilized this instrument as a dependent measure.…”
Section: Methodsmentioning
confidence: 99%